D’un projet d’observatoire démographique à l’élaboration d’une plateforme : comment l’usage de technologies numériques a transformé nos relations disciplinaires - Sébastien Oliveau; Yoann Doignon; Isabelle Blöss-Widmer (Humanités Numériques)
This article explains how the introduction of a digital tool has profoundly transformed a research approach that aimed to study Mediterranean populations from demographic, geographical and statistical perspectives. The authors first present the digital platform that enabled the project to bring together researchers from different disciplines to discuss their subject. The presentation of the digital tool we developed is an opportunity to remind that technological choices are disciplinary choices. Finally, the article describes the effects of these technological choices on research methods, showing how our conversations about a tool led to a hybridization of disciplines and ultimately to an original research approach, which was not simply interdisciplinary, but truly transdisciplinary.